Stroke seasonality associations with subtype, etiology and laboratory results in the Ludwigshafen Stroke Study (LuSSt) - Palm, Frederick; Martins dos Santos, Michael; Urbanek, Christian; Greulich, Matthias; Zimmer, Kathrin; Safer, Anton; Grau, Armin J.; Becher, Heiko (European journal of epidemiology, 2013)
Data on seasonal differences in stroke incidence are conflicting. Little is known about seasonal variability in etiological stroke subtypes and population-based data on possible trigger factors are lacking. The Ludwigshafen Stroke Study is a prospective population-based stroke registry. All residents of the city of Ludwigshafen who suffer from acute stroke or TIA are registered. Patients with first-ever stroke (FES) were included for the present analysis. Between January 1, 2006 and December 31st, 2010, 1,779 patients (age 71.7 ± 13.4 years (mean + standard deviation; 897 (50.4 %) women) suffered a FES. Incidence for FES was lowest in summer (reference) with significantly higher rates in winter (rate ratio (RR) 1.20, 95 % confidence interval (CI) 1.05-1.37) and spring (RR 1.21 95 % CI 1.06-1.38). First-ever ischemic stroke (FEIS) was more common in winter (RR 1.16, 95 %CI 1.01-1.34) and first-ever intracerebral haemorrhage (FE-ICH) was more frequent in spring (RR 2.0, 95 %CI 1.24-3.22) than in summer. In FES, systolic and diastolic blood pressure on admission (SBP/DBP) showed significant variation with lowest values in summer (SBP: p = 0.02; DBP p = 0.05). In subtypes of FEIS, cardioembolism tended to be more common in winter (p = 0.14). There were no differences in risk factor prevalence between seasons. Leukocyte count on admission was lowest in summer (8.2 ± 1.4/μl) and highest in winter (8.9 ± 1.9/μl; p = 0.008). The hematocrit showed a similar trend (p = 0.06). Our data show higher incidence rates for FES in winter and spring, for FEIS in winter and for FE-ICH in spring. Variations in blood pressure on admission and leukocyte counts were associated with these findings and may possibly contribute to seasonal stroke variability.
Gesehen am 16.12.2021